Strategies and guidelines for urban sustainability: the Covid-19 effects on the mobility system in Italy - Federica Gaglione (TeMA: Journal of Land Use, Mobility and Environment, 2020)
The emergency at COVID-19 has changed the face of our cities, preventing most urban activities, limiting travel on large, medium and short distances and drastically reducing the number and intensity of social relationships. The organization of the built environment, combined with the characteristics of the pedestrian network, has taken on greater weight in relation to the restrictive measures that COVID-19 has imposed on entire populations.